A Study on the Two-way Causal Relationship Between Industrial Structure Evolution and Economic Growth: Empirical Test Based on 40 Years of Reform and Opening-up in China. (January 2019) - Liu, Qingjie; Hu, Biliang
The adjustment of industrial structure is an important engine driving the economic growth. The relationship between industrial structure evolution and economic growth is characterized by various stages. The article uses the data of 31 provincial units in China from 1978 to 2016 as a sample, divided into five stages with time as nodes, and takes the rationalization and optimization of industrial structure (OIS) as indicators to measure the adjustment of industrial structure. The main research conclusions are obtained through cointegration test, Granger test and simultaneous equation model. Results indicate that the relationship between OIS and economic growth shows the characteristics of mutual influence, while the rationalization of industrial structure unilaterally affects economic growth. Rationalization of industrial structure has significantly stimulated economic growth, especially in the past 10 years after China's accession to the World Trade Organization (WTO). The stimulating effect of OIS on China's economic growth has not yet been fully demonstrated. This indicates that the OIS, as a new momentum of economic growth, has not yet been brought into presently in China. Economic growth has a driving effect on the OIS. However, it is only when the economic development enters a relatively mature stage can this driving effect be gradually brought into play.